Long-term indoor-outdoor aerosol measurement in Helsinki, Finland - Hussein, T.; Hämeri, K.; Kulmala, M. (Boreal Environment Research Publishing Board, 2024)
Total aerosol number concentration measurements were carried out with a condensation particle counter in a Helsinki suburban area throughout the period from 1 November 1999 to 30 June 2000. The variation of the aerosol concentration was investigated in connection with the season, meteorological conditions and traffic activity, which were concluded as the main factors affecting the outdoor aerosol concentrations. In addition, the indoor-outdoor connection was investigated based on the indoor/outdoor (I/O) concentration ratio. Two daily patterns of the total aerosol number concentration were observed in each season, one for weekdays and another for weekends. On average, the submicron aerosol number concentration was at its highest during the winter and lowest during the summer. The temporal variation of the total aerosol number concentration indoors followed the outdoor variation with a small delay. Larger I/O ratios (average 0.66) were observed during the summer than during the winter and the spring (average 0.58).